2012
DOI: 10.1371/journal.pone.0050716
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, Pharmacodynamics and Pharmacokinetics of Umeclidinium and Vilanterol Alone and in Combination: A Randomized Crossover Trial

Abstract: Umeclidinium bromide (GSK573719; UMEC), a new long-acting muscarinic receptor antagonist (LAMA), is in development with vilanterol (GW642444; VI), a selective long-acting β2 agonist (LABA), as a once-daily inhaled combination therapy for the treatment of chronic obstructive pulmonary disease (COPD). A single dose healthy volunteer study was conducted to assess the safety and tolerability, pharmacodynamics (PD) and pharmacokinetics (PK) of inhaled umeclidinium (500 µg) and vilanterol (50 µg) when administered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 13 publications
5
27
0
1
Order By: Relevance
“…Single-dose studies of UMEC and VI coadministration, and UMEC 10-350 mcg demonstrated rapid UMEC absorption (t max 5-15 min) [16,22]. A t of 1.56 h and 1.78 h has been reported for UMEC 500 mcg alone and UMEC/VI 500/50 mcg, respectively [16], while UMEC 10-350 mcg has demonstrated a mean urine t of 6-10 h [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-dose studies of UMEC and VI coadministration, and UMEC 10-350 mcg demonstrated rapid UMEC absorption (t max 5-15 min) [16,22]. A t of 1.56 h and 1.78 h has been reported for UMEC 500 mcg alone and UMEC/VI 500/50 mcg, respectively [16], while UMEC 10-350 mcg has demonstrated a mean urine t of 6-10 h [24].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive data characterizing the safety, pharmacology, and pharmacokinetics (PK) of FF and UMEC were generated in studies in healthy volunteers and patients with asthma and COPD as part of the development program for FF/VI and UMEC/VI [14][15][16][17][18]. To apply these data to guide the development of the FF/UMEC combination, it is necessary to characterize any pharmaceutical and/or PK interactions that result when two active components are administered simultaneously through a single device.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,7,8,[10][11][12][13][14] There was no difference in vilanterol T max when delivered as monotherapy or in combination. 12 The steady state of umeclidinium/vilanterol is achieved within 14 days, with 1.8-and 1.7-fold accumulation, respectively. 1 However, there is very little increase in maximum serum concentration from days 7 to 14.…”
Section: Pharmacokineticsmentioning
confidence: 93%
“…In a single-dose healthy subject Japanese study, UMEC (500µg) and VIL (50µg) monotherapy, and in combination (UMEC/VIL) were reported to have no marked systemic exposures or tolerability issues [21].More recently an open-labeled, randomized, crossover study to assess the pharmacokinetics, safety and tolerability of 2 inhaled UMEC/VIL combinations (62.5/25 and 125/25-µg) compared to their monocomponents (UMEC -62.5 and 125µg; VIL -25µg) in 20 healthy Chinese subjects has been conducted [22]. Following repeat VIL dosing, time to maximum plasma concentration (tmax) was five minutes; with its accumulation at 25-66% of maximum plasma concentration (Cmax) and 17 to 43% based on AUC (0-2).…”
Section: Pharmacokinetics Of Vilmentioning
confidence: 99%